Health disparity and cancer health disparity in China - Qi Wang; Jie Jiao (Elsevier, 2016)
China is one of the largest and most populated countries in the world. It has undergone rapid economic growth in recent years. However, the development is not equitable, and the distribution of wealth significantly varies among the regions in China. Geographical and socioeconomic inequalities, together with the lack of an equitable national social support system, cause the high variance of health outcomes among the regions. Furthermore, the fast growth of the economy has evoked many environmental challenges and puts much pressure on the population. The severe environmental deterioration, especially of the atmosphere and water bodies, has affected the health of the people living in China. As a result, cancer has become a major public health issue, and an alarming increase in incidence and mortality has been reported. However, cancer incidence and mortality vary in different areas in China. Cancer and cancer treatment disparities have existed for years. This article will discuss the existing health and cancer disparities associated with the risk factors and how these disparities are managed in China.